Carbon Fiber/Carbon Nanotube Buckypaper Interply Hybrid Composites: Manufacturing Process and Tensile Properties1. Issue 10 (19th March 2015) - Wang, Shaokai; Downes, Rebekah; Young, Charles; Haldane, David; Hao, Ayou; Liang, Richard; Wang, Ben; Zhang, Chuck; Maskell, Rob
<x xml:space="preserve">Abstract</x> This paper reports on a study of carbon nanotube (CNT) thin film, or buckypaper (BP), integrated into carbon fiber (CF) prepreg composites to create hybrid composite materials with high CNT content. The autoclave process of manufacturing hybrid composite laminates was investigated to gain an understanding of nano/micro dual‐scale resin flow characteristics. The study found that resin bleeding along the through‐thickness direction was inhibited due to extra‐low permeability and high resin absorbing capacity of the BP. Resin matrix‐impregnated BP layers were much thicker than dry pristine BP due to high resin absorbency and swelling effects. The BP/unidirectional carbon fiber (UD‐CF) hybrid composites with local fiber volume fraction of 61.46 vol% in CF ply and local CNT volume fraction of 26.57 vol% in BP layer, had a tensile strength of 2519 ± 101 MPa and modulus of 149 ± 18 GPa. The dramatic improvements in both in‐plane and through‐thickness electrical conductivities demonstrate potential for both structural and multifunctional applications of the resultant hybrid composites.